Comparing shapes of Engel curves - Andreas Chai; Alessio Moneta (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We measure how different the shapes of Engel curves are across 59 commodity groups. The same analysis is carried out for their derivatives and variances. While Engel curves possess a relatively homogeneous shape, significantly more heterogeneity is present in derivatives and when particular sub-classes of income are considered.
Keywords: D12; C14; 330; Consumption; Kernel method; rank correlation; Curve shape; Mikroökonomische Konsumfunktion; Verbraucherausgaben; Schätzung; Produkt; Großbritannien